Single‐Molecule Charge‐Transport Modulation Induced by Steric Effects of Side Alkyl Chains. Issue 24 (27th October 2021) - Jiang, Wenlin; Tan, Zhibing; Almughathawi, Renad; Wu, Qingqing; Liu, Zitong; Liu, Junyang; Hou, Songjun; Zhang, Guanxin; Lambert, Colin J.; Hong, Wenjing; Zhang, Deqing
Abstract: The experimental investigation of side‐chain effects on intramolecular charge transport in π‐conjugated molecules is essential but remains challenging. Herein, the dependence of intra‐molecular conductance on the nature of branching alkyl chains is investigated through a combination of the scanning tunneling microscope break junction (STM‐BJ) technique and density functional theory. Three thiophene‐flanked diketopyrrolopyrrole (DPP) derivatives with different branching alkyl chains (isopentane, 3‐methylheptane, and 9‐methylnonadecane) are used with phenylthiomethyl groups as the anchoring groups. The results of single‐molecule conductance measurements show that as the alkyl chain becomes longer, the torsional angles between the aromatic rings increase due to steric crowding, and therefore, the molecular conductance of DPP decreases due to reduction in conjugation. Both theoretical simulations and 1 H NMR spectra demonstrate that the planarity of the DPPs is directly reduced after introducing longer branching alkyl chains, which leads to a reduced conductance. This work indicates that the effect of the insulating side chain on the single‐molecule conductance cannot be neglected, which should be considered for the design of future organic semiconducting materials. Abstract : Intra‐molecular conductance variations observed upon varying the type of branching alkyl chains were investigated by scanning tunneling microscopy. Both theoretical simulations and 1 H NMR spectra‐demonstrate that the planarity of the conjugated molecule is directly reduced after introducing longer branching alkyl chains, causing a reduced conductance. This work provides a way to control single‐molecule conductance, which should be considered for future organic semiconducting material design.